[Country Church Near Búðir] - Streng, Evelyn Fiedler (1975)
Photograph of a country church near Búðir, Iceland. The white church with a red roof sits on a dark, grassy hill surrounded by fog. A rectangular tower lined with red sits toward the front of the church beside a front entrance offshoot. A simple wooden fence surrounds the church yard full of bushy grass. A person walks along the hill to the right wearing a dark jacket and jeans.